Integritas Ittiba’ terhadap Public Figure dalam Era Post-Truth : Telaah Kritis Berdasarkan Al-Qur'an dan Hadis - Ibnu Khaldun; Desy Helma Permata (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2024)
This study examines the concept of ittiba’ integrity towards public figures in the context of the post-truth era, using a critical approach based on the Al-Qur'an and Hadith. The concept of ittiba’ refers to the act of following true teachings and examples, as outlined in the Al-Qur'an and Hadith. In the post-truth era, where truth is often obscured by false narratives, ittiba’ integrity becomes crucial to ensure the honesty and exemplary behaviour of public figures. This research critically analyses the concept of ittiba’ in the context of modern social and political dynamics, with a focus on defending against slander and the dissemination of false information. The findings of this study are expected to provide deeper insights into the importance of ittiba’ integrity in upholding truth and exemplary conduct in a modern society filled with post-truth challenges.